Changes in Apoptosis-Related Proteins in The Urothelium of Rat Bladder Following Partial Bladder Outlet Obstruction and Subsequent Relief - Park, Jong Mok; Lee, Ji Yong; Na, Yong gil; Song, Ki Hak; Lim, Jae sung; Yang, Seung Woo; Lee, Seung-Hwan; Kim, Gun-Hwa; Shin, Ju Hyun (Urology Journal, 2020)
Purpose: Partial bladder outlet obstruction (PBOO) induces sustained bladder over-distension, leading to ischemia/reperfusion (I/R)-related oxidative damage of the urothelium via apoptosis. The present study aimed to investigate the sequential course of apoptosis in the urothelium of rat bladder and identify the changes in apoptosis-related proteins during PBOO and subsequent relief. Materials and Methods: The study was conducted using 60 female Sprague-Dawley rats divided into three groups: sham-operated, PBOO only, and PBOO plus subsequent relief. PBOO was induced for 2 weeks, and then the obstruction was relieved by removal of the ligature. The urothelium was assessed by a histological analysis, and expression levels of apoptosis-related proteins were detected by quantitative PCR and immunoblotting. Results: Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL)-positive cells were significantly increased in the PBOO only group when compared with the sham-operated group, and decreased in the PBOO relief group when compared with the PBOO group (P < 0.001). From the quantitative PCR and the western blot analyses, expression of Bax, caspase-3, P38, and Jnk was significantly increased in the PBOO group (P < 0.001). However, expression of Erk, Bcl-2 significantly decreased in the PBOO group (P < 0.001). The expression of Erk and Bcl-2 significantly increased in the PBOO relief group when compared with the PBOO group (P < 0.001). In comparison to the sham-operated group, expression levels of survivin significantly increased in both the PBOO and PBOO plus relief groups (P < 0.001). In addition, the expression levels were significantly different between the PBOO and PBOO plus relief groups (P < 0.001). Conclusion: PBOO induced apoptosis of urothelium is related to alterations in the MAPK signaling pathways and apoptosis-related protein change. These results may also suggest that the pro-survival Erk signaling cascade and the expression survivin are activated in response to ischemic bladder injury and associated with initiation of bladder restoration in PBOO and subsequent relief. However, the mechanism of survivin as anti-apoptotic protein in ischemic bladder injuries remains unclear.